Contextualizing writing activities and exploring literary texts on The Portal for Teachers of Portuguese as a Foreign Language/Non-Mother Tongue - Desirée Oliveira (Journal of the National Council of Less Commonly Taught Languages)
This study analyzes 425 didactic units published on the Portal for Teachers of Portuguese as a Foreign Language/Non-Mother Tongue, created by the International Portuguese Language Institute to provide teaching materials that represent various Portuguese-speaking countries. The analysis addresses the following questions: 1) How is contextual information integrated into prompts for writing activities within the didactic units? 2) What approach is used for teaching literary texts in the didactic units? The examination draws on the theoretical contributions of scholars such as Bakhtin (1997), Bronckart (1999), and Cosson (2006). The findings reveal that most prompts for writing activities lack sufficient contextual information and that literary texts could benefit from a more in-depth exploration. Recommendations are provided to improve both prompts for writing activities and the treatment of literary texts in these instructional resources.